An assessment of soil respiration on two contrasting urban forestry areas using the SolvitaTM Gel System. Issue 2 (3rd April 2019) - Hardy, Kit; Weir, Irene; Slater, Duncan
ABSTRACT: Inadequate soil conditions can affect tree health and longevity but there are few tools available to urban foresters to carry out soil assessments. The Solvita TM Gel System field test, developed for agricultural purposes, assesses biological activity in soil samples by measuring CO2 respiration rates.  This test was used alongside other analytical tests using soil samples from two contrasting urban sites; a wooded area and a grassed area with semi-mature trees. The wooded site had 156% higher levels of NPK, 240% more soil organic matter and 252% more easily oxidisable soil organic carbon than the grassed site. In addition, the Solvita TM Digital Colour Reader value and basal respiration was 196% higher for the wooded site. Soil bulk densities were recorded at 0.97 g cm -3 and 1.45 g cm -3 for the wooded and grassed sites respectively. There were significant correlations between basal respiration results and soil organic matter content. A calibrating laboratory experiment identified significant differences in Solvita TM test values between five soil sample groups with increasing leaf mould content. We conclude that the Solvita TM Gel System field test has the potential to be used as an urban forest soil assessment tool and its use warrants further research.